DURABILITY FATIGUE PREDICTION AND STRUCTURE OPTIMIZATION OF LOAD-BEARING KEY PART OF TRACKED VEHICLE - YAN SiHong; TAO FengHe; JIA ChangZhi (Jixie qiangdu)
Strat from the structure of torsion shaft to more reasonably use durability and design life,realize the various optimization of mechanical construction.A parameterized model of torsion shaft was developed based on Solidworks and imported into ANSYS Workbench by data interface.Transient stress and durability fatigue of parameterized model were analyzed in ANSYS Workbench.The multi objective optimization of torsion shaft was designed in Design Exploration module and the optimized structure of torsion shaft was reanalyzed in ANSYS Workbench.The result of optimization design shows that optimization model meets durability life of torsion shaft and weight decreased 9.9 percent.The result demonstrates the correctness of the optimization.